Promoting student persistence and academic success: Implications for higher education institutions - Plessis, Davy J Du; Santana, Engelbert; Hill, Macsu (American Journal of Social Sciences and Humanities, 2023)
There are numerous factors which have a role in impacting students’ experiences at higher education institutions. The study’s main objectives are to determine which support structures at institutions of higher learning promote a conducive environment for student success. Secondly, to explore activities that institutions of higher learning can consider when addressing the issue of academic success. The paper focuses on the Honors Living-Learning Community (HLLC) at Rutgers University – Newark (RU-N), New Jersey as a case study to examine how it successfully ensures its students’ academic success. A self-report survey was conducted to examine the experiences of HLLC alumni to identify factors impacting students’ academic success. The 2018 to 2021 alumni at the Honors Living-Learning Community (HLLC) at Rutgers University – Newark (RU-N) were the population for this study. The study opted for the theoretical framework of Tinto and Pusser; two noted theorists on student success and persistence. The study’s findings suggest that maintaining institutional commitment, enhancing academic and social support, diversifying the curriculum, implementing longitudinal assessments, investing in faculty development, and promoting alumni engagement as ways to improve the HLLC’s impact on student success. By implementing the proposed recommendations, the HLLC can allow students to achieve academic success, grow personally, and positively impact their communities. The HLLC is a beacon of hope for higher education because it continues to shape students’ lives and ensure that students can attain their undergrade education within four years to help reduce the financial burden on all stakeholders in higher education.